ADVOKASI HUKUM OLEH LEMBAGA PERLINDUNGAN ANAK INDONESIA (LPAI) - Lubis, Fauziah; Iskandar, Muhammad Rafa; Prishela, Cindy Salwa; Putri, Mey Nisa; Siregar, Desi Pitriani; Sumitro, Dimas (Gapenas Publisher, 2025)
This paper discusses the forms of legal advocacy and efforts that can be made to strengthen legal advocacy carried out by LPAI. The author found that LPAI has actively carried out legal advocacy in the form of lobbying in the form of counseling and education to the community about children's rights and how to identify and report cases of violence or exploitation of children. Through these programs, they try to raise awareness of the need to protect children from all forms of threats they may face. This study analyzes the efforts of child protection institutions in Indonesia in protecting victims of sexual abuse. Using qualitative analysis methods on related data, the main conclusion of this study is that child protection institutions face a number of obstacles that limit their effectiveness in providing adequate protection for victims of sexual abuse. These obstacles include limited resources, lack of coordination between institutions, low public awareness, limited access to protection services, and inconsistent implementation of the law